AN ANALYSIS OF NAKETI TRADITION AS A MEANS OF HEALING THE SICK AND FORGIVING - Aryanto Toabnani; Nikolas Arlando Boyfala; Eugelin Sulaiman; Erlinda Sonya Pale (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
The purpose of this study was to examine the naketi tradition as a means for healing the sick (a means that bridges the guilty man with hand to God as the creator so that the drugs used for healing can work properly). The things that never harmed other people and as an excuse for the Dawan tribe can be seen in form of the stages of forgiveness. The research method used in this study is a qualitative descriptive method, which is examining an object by collecting, describing and analysing the data based on facts and then drawing conclusions according to the research objectives. In collecting the data, the writer used observation and interview techniques. The result of the study shows that the Naketi tradition is the original culture or custom of the atoin meto or dawan tribe. Naketi is believed to be a way out of conflicted communities so that they can get out from the problems they face. Naketi has been inherited by the ancestors and is a community obligation to be guarded and preserved.